2020
DOI: 10.1136/acupmed-2017-011459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electroacupuncture on sedation requirements during colonoscopy: a prospective placebo-controlled randomised trial

Abstract: Introduction: Propofol provides excellent sedation during colonoscopy. However, its application, namely when used together with an opioid, is associated with cardiopulmonary depression. Acupuncture is used nowadays for the treatment of pain and anxiety, and also to induce sedation. We hypothesised that electroacupuncture (EA) during colonoscopy would have sedative effects, thereby reducing propofol requirements to achieve an adequate level of sedation. Method: The study was designed and conducted as a single c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Full-text screening of the remaining 36 articles was performed, resulting in eight articles being selected for inclusion in the metaanalysis (Fig. 1) [13][14][15][16][22][23][24][25]. The j value was 0.87, indicating a high degree of agreement between the two reviewers.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Full-text screening of the remaining 36 articles was performed, resulting in eight articles being selected for inclusion in the metaanalysis (Fig. 1) [13][14][15][16][22][23][24][25]. The j value was 0.87, indicating a high degree of agreement between the two reviewers.…”
Section: Search Resultsmentioning
confidence: 99%
“…Interventions in the treatment groups included acupuncture [22][23][24][25], EA [13,16], and TEAS [14,15]. Interventions in the control groups included SA [13,22,25], PA [13], sham TEAS [14,15], no acupuncture [22][23][24][25], and no EA [16]. Six of the studies had Jadad scores C 3 [13][14][15][22][23][24].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…6,16,17 However, stimulating at a single frequency may cause subject to habituated to the stimulation and hence reduce the effect of EA. 18 It was reported that the therapeutic effect of EA may be maximized when stimulations were given in dense-disperse mode, in which the stimulation was alternating between 2 frequencies. Hence, in this work, we chose 2-/10-Hz dense-disperse wave to stimulate the selected acupoints.…”
Section: Experimental Designmentioning
confidence: 99%